The Impact of Oil Prices on the Stock Market and Real Exchange Rate: The Case of Kazakhstan - Kelesbayev, Dinmukhamed; Myrzabekkyzy, Kundyz; Bolganbayev, Artur; Baimaganbetov, Sabit (International Journal of Energy Economics and Policy, 2022)
In this study, the relationship between KASE stock market closing prices and oil prices is analyzed using ADF and Zivot-Andrews’ (1992) unit root tests and monthly data for the period of 2016-2021. First, the variables are tested for causality. Results show that there is a causal relationship between the real exchange rate and closing prices and between oil prices and the real exchange rate. The short-term effects of the variables are investigated using the VAR method. Results show that Brent crude oil prices have a positive effect on KASE closing prices, while the real exchange rate has a negative effect. In conclusion, changes in oil prices affect the formation of stock prices.